A spinach O-acetylserine(thiol)lyase homologue, SoCSaseLP, suppresses cysteine biosynthesis catalysed by other enzyme isoforms - Noda, Miki (Biochim Open, 2016)
An enzyme, O-acetylserine(thiol)lyase (OASTL), also known as O-acetylserine sulfhydrylase or cysteine synthase (CSase), catalyses the incorporation of sulfide into O-acetylserine and produces cysteine. We previously identified a cDNA encoding an OASTL-like protein from Spinacia oleracea, (SoCSaseLP), but a recombinant SoCSaseLP produced in Escherichia coli did not show OASTL activity. The exon-intron structure of the SoCSaseLP gene shared conserved structures with other spinach OASTL genes. The SoCSaseLP and a Beta vulgaris homologue protein, KMT13462, comprise a unique clade in the phylogenetic tree of the OASTL family. Interestingly, when the SoCSaseLP gene was expressed in tobacco plants, total OASTL activity in tobacco leaves was reduced. This reduction in total OASTL activity was most likely caused by interference by SoCSaseLP with cytosolic OASTL. To investigate the possible interaction of SoCSaseLP with a spinach cytosolic OASTL isoform SoCSaseA, a pull-down assay was carried out. The recombinant glutathione S-transferase (GST)-SoCSaseLP fusion protein was expressed in E. coli together with the histidine-tagged SoCSaseA protein, and the protein extract was subjected to glutathione affinity chromatography. The histidine-tagged SoCSaseA was co-purified with the GST-SoCSaseLP fusion protein, indicating the binding of SoCSaseLP to SoCSaseA. Consistent with this interaction, the OASTL activity of the co-purified SoCSaseA was reduced compared with the activity of SoCSaseA that was purified on its own. These results strongly suggest that SoCSaseLP negatively regulates the activity of other cytosolic OASTL family members by direct interaction.